2005
DOI: 10.1111/j.1461-0248.2004.00711.x
|View full text |Cite
|
Sign up to set email alerts
|

Belowground organism activities affect plant aboveground phenotype, inducing plant tolerance to parasites

Abstract: International audienceSoil fauna activities are probably more important than currently acknowledged in determining individual plant response to stresses and overall plant diversity. Here we demonstrate that the positive effect of earthworms on rice could be the result of a systemic effect on plant physiology. Moreover, this effect could improve tolerance to stressors such as parasitic nematodes. In a controlled experiment, an 82% decrease in the production of infested plants was suppressed when earthworms were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
74
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(80 citation statements)
references
References 39 publications
1
74
0
4
Order By: Relevance
“…While sulfur-containing glucosinolates were reduced by earthworms in Brassica oleracea leaves (Wurst et al, 2006), aliphatic glucosinolates were reduced and aromatic glucosinolates were enhanced in Sinapis alba (Lohmann et al, 2009). Blouin et al (2005) showed that earthworms can change stress-responsive gene expression (such as genes coding for lipoxygenase and cysteine protease) and make rice ( Oryza sativa ) plants more resistant to root-feeding nematodes.…”
Section: Mechanisms Of How Detritivores Affect Plant and Aboveground mentioning
confidence: 99%
“…While sulfur-containing glucosinolates were reduced by earthworms in Brassica oleracea leaves (Wurst et al, 2006), aliphatic glucosinolates were reduced and aromatic glucosinolates were enhanced in Sinapis alba (Lohmann et al, 2009). Blouin et al (2005) showed that earthworms can change stress-responsive gene expression (such as genes coding for lipoxygenase and cysteine protease) and make rice ( Oryza sativa ) plants more resistant to root-feeding nematodes.…”
Section: Mechanisms Of How Detritivores Affect Plant and Aboveground mentioning
confidence: 99%
“…Earthworms can have either a direct (e.g., by ingestion) or an indirect (i.e., by physical and chemical changes of soil properties) impact on plant-feeding nematodes (Blouin et al, 2005;Lafont et al, 2007;Senapati, 1992;Wurst, 2010). Under laboratory conditions, Boyer et al (2013) revealed a decrease in Heterodera sacchari and Pratylenchus zeae populations, two plant parasitic nematodes, in the presence of P. corethrurus.…”
Section: Effect On Nematodesmentioning
confidence: 99%
“…According to some authors, the latter leads to the release of mineral nitrogen essentially and represents the major mechanism of action of earthworms responsible for increases in plant biomass production . It could explain how greater benefits on productivity have mostly been observed in poor soils (Brown et al, 2004). However, in an experimental system combining rice plants and the earthworm Millsonia anomala, increasing the availability of mineral nutrients did not suppressed the positive effect of the earthworm on plant growth (Blouin et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Since decaying earthworms were not a possible source of additional N (worms survival rates were 100%), the majority of the extra N was probably formed through mineralization of soil organic matter by gut-associated and cast-associated micro-organisms, in accordance with Brown's hypothesis that earthworms mostly increase plant growth through N mineralization . However, recent evidence have started an ongoing and fascinating debate of whether enhanced mineralization alone provides a full explanation for the growth stimulation (Brown et al, 2004;Scheu, 2003;Blouin et al, 2006).…”
Section: Earthworms Can Reverse Most Effects Of Poor Soil Quality On mentioning
confidence: 99%
See 1 more Smart Citation